(untitled) (International Journal of Research on Service-Learning in Teacher Education, 2010)
Service-learning at its best: Life isnt fair, and people dont always get what they deserve. How far are we going to let people fall before we say this is not acceptable? Service-learning at its worst: I dont understand. If unemployment is so high on the reservation, how come we are painting their houses? These quotes, and others like them, were the catalyst for my investigation into the upside and downside of service-learning and the source of my inspiration and motivation to write this book. This book shares my experience, research findings, and conclusions on service-learning and social justice in an accessible, straightforward manner that is useful to elementary and secondary teachers, administrators, university professors, and preservice teachers. As a high-school classroom teacher and administrator, a recent doctoral student, and an adjunct college professor, I draw on my varied experience to offer a framework including theory (how things work) and practice (what you can do) to build a service-learning program that fosters students critical consciousness and their commitment to engage in social change. I hope you find this thought provoking and helpful. The French teacher in me says Bon Courage!; and, as my dad always used to say, Sempre Avanti!